Health status of househelps living in the semi-urban area of Goa - Prabhu, Aadini V.; Shah, Hemangini K. (International Journal Of Community Medicine And Public Health, 2021)
Background: The world’s population is on the rise and so is the need for good housing and job opportunities. This has led to an increase in the number and overcrowding of existing slums which lack reliable sanitation and hygiene. People who work as househelps take on the responsibilities of the households where they work and their own families. The study was undertaken to determine the health status and quality of life of househelps residing in Goa. Methods: A Community based cross sectional study was carried out among househelps living in the semi-urban area of Goa. Participants were selected via snowball sampling. Information was collected through a predetermined questionnaire and via medical examination, after initial briefing. The data was compiled; analyzed and appropriate statistical tests were applied. Results: Marriage before 20 years of age was noted in majority (70.2%). Poor housing standards were noticed in 94%.64% had increased working hours. 80% of the househelps had health complaints of backache, menstrual problems, fever. Statistically significant difference was observed between daily working hours and morbidity, and between age of marriage and number of children. Number of children and morbidity also showed significant statistical relationship. Conclusions: The study highlights the problems faced by the domestic helps which can be tackled by implementing laws which recognize them as a part of the organized sector, holding health camps in rural areas, increasing awareness about the diseases spread in an unhygienic environment.